Tissue metabolomics reveals metabolic dysregulation associated with intimal hyperplasia in arteriovenous fistula stenosis - Zhao, Ming; Wu, Qixin; Zhao, Yifei; Nian, Rui; Li, Wanjun; Lu, Hongzhao (Frontiers in Physiology, 2025)
ObjectiveThis study performed untargeted LC-MS metabolomics on venous tissues from maintenance hemodialysis patients undergoing arteriovenous fistula (AVF) reconstruction surgery.MethodsA total of six stenotic and six non-stenotic AVF tissues were analyzed. Paired samples were collected from stenotic AVF segments and non-stenotic regions (control group). Histological analysis revealed significant intimal hyperplasia in stenotic tissues (687.90 ± 149.00 μm vs. 286.70 ± 95.18 μm, P < 0.0001 by HE staining) and excessive collagen deposition (Masson staining).ResultsMetabolomic profiling identified 802 metabolites, with 356 differentially expressed (VIP > 1, P < 0.05), predominantly lipids/lipid-like molecules. KEGG enrichment highlighted five dysregulated pathways (P < 0.01): Arginine/proline metabolism; Glycerophospholipid metabolism; ABC transporters; Choline metabolism in cancer; Retrograde endocannabinoid signaling. Six metabolites showed perfect diagnostic potential (AUC = 1.0): niacin, free carnitine, 3-hydroxynonyl-5,7-dienoylcarnitine, 3-methylheptanediylcarnitine, dec-7-enoylcarnitine, and γ-aminobutyric acid. Significant metabolite-clinical correlations included: Choline positively correlating with serum phosphorus (r = 0.62, P = 0.008); Carnitine associating with hemoglobin levels (r = 0.58, P = 0.012).ConclusionThis tissue-based metabolomics study defines specific metabolic disturbances driving AVF stenosis, proposing mechanistic insights and candidate biomarkers.